Decoding restricted participation in sequential electricity markets - Andreas Knaut; Martin Heinrich Paschmann (Institute of Energy Economics at the University of Cologne (EWI), 2017)
Restricted participation in sequential markets may cause high price volatility and welfare losses. In this paper we therefore analyze the drivers of restricted participation in the German intraday auctin which is a short-term electricity market with quarter-hourly products. Applying a fundamental electricity market model with 15-minute temporal resolution, we identify the lack of sub-hourly market coupling being the most relevant driver and restricted participation. We derive a proxy for price volatility and find that full market coupling may trigger quarter-hourly price valatility to decrease by a factor close to four.
Keywords: C13; C51; D44; D47; L94; Q21; Q41; 330; sequential electricity markets; short-term market dynamics; electricity market interaction; short-term price formation; restricted market participation; price volatility